2009
DOI: 10.1111/j.1600-0404.1985.tb03182.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an aldose reductase inhibitor (Sorbinil®) on diabetic neuropathy and neural function of the retina: a double-blind study

Abstract: 37 patients with diabetic neuropathy were randomized into 2 equal groups and given daily doses of 200 rng or 50 mg of Sorbinil@a potent aldosereductase inhibitorin a double-blind 4-week period between 2 periods on placebo.The purpose was to assess the role of the drug on various neurophysiological parameters and its clinical effect. No difference was shown either in the placebo periods compared to Sorbinil treatment or between the 2 groups on the neurophysiological parameters but there was a statistically sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Regarding ranirestat, also, there is an RCT showing that the drug was effective for the treatment of mild to moderate motor neuropathy but that its effects did not differ significantly compared with those of placebo for the treatment of sensory neuropathy and an RCT reporting improvements in sensory and motor nerve functions Concerning sorbinil, there are two RCT reporting no effect and a non‐randomized comparative trial reporting no effect. Thus, the effectiveness of ARI for the management of neuropathy varies among drugs.…”
Section: Cq17: Are Aldose Reductase Inhibitors (Ari) Useful For the Tmentioning
confidence: 99%
“…Regarding ranirestat, also, there is an RCT showing that the drug was effective for the treatment of mild to moderate motor neuropathy but that its effects did not differ significantly compared with those of placebo for the treatment of sensory neuropathy and an RCT reporting improvements in sensory and motor nerve functions Concerning sorbinil, there are two RCT reporting no effect and a non‐randomized comparative trial reporting no effect. Thus, the effectiveness of ARI for the management of neuropathy varies among drugs.…”
Section: Cq17: Are Aldose Reductase Inhibitors (Ari) Useful For the Tmentioning
confidence: 99%
“…Controlled studies of aldose reductase inhibitors (ARIs) have failed to produce any real insight into their potential efficacy in the treatment of human diabetic neuropathy. Early studies with sorbinil showed modest improvements in nerve conduction velocity (NCV) ( Judzewitsch et al, 1983; Christensen et al, 1985; O‘Hare et al, 1988 ) , and some improvement in autonomic function has been reported ( Sundkvist et al, 1987; Roy et al, 1990 ) . In addition, sorbinil has been shown to improve pain scores in patients suffering from chronic painful diabetic neuropathy ( Young et al, 1983 ) .…”
Section: Introductionmentioning
confidence: 99%